1970
DOI: 10.1295/polymj.1.395
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization of Aromatic Aldehydes. V. Cationic Cyclopolymerization of o-Vinylbenzaldehyde

Abstract: Polymerization of o-vinylbenzaldehyde was carried out at 0°C with BFaOEt2 catalyst. The polymers obtained as white powders were soluble in common organic solvents, and were not cleaved by treatment with dilute hydrochloric acid. The degree of polymerization was 20-30. The polymer contained approximately 20% of the pendent vinyl group and 5% of the pendent aldehyde group. The rest of the monomer unit was presumably the cyclized unit. On the basis of these structural data, a cationic propagation scheme of o-VBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

1971
1971
2012
2012

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
2
11
0
Order By: Relevance
“…These results indicated that the copolymers had no BzA-BzA sequences, and were consistent with previous reports that BzA homopolymerization did not proceed. [10][11][12][13] On the other hand, copolymerization failed in polar solvents such as dichloromethane, at 0 C, and/or in the absence of an added base. In these cases, only IBVE homopolymers were obtained, as confirmed by 1 H NMR analysis.…”
Section: Copolymerization Of Bza With Ibve Using Various Lewis Acidsmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicated that the copolymers had no BzA-BzA sequences, and were consistent with previous reports that BzA homopolymerization did not proceed. [10][11][12][13] On the other hand, copolymerization failed in polar solvents such as dichloromethane, at 0 C, and/or in the absence of an added base. In these cases, only IBVE homopolymers were obtained, as confirmed by 1 H NMR analysis.…”
Section: Copolymerization Of Bza With Ibve Using Various Lewis Acidsmentioning
confidence: 99%
“…[10][11][12] In fact, their homopolymerizations have never been achieved except in the case of benzaldehyde (BzA) derivatives with special structures. 10,12,13 In contrast, polymers were obtained from both BzA and a simple derivative in copolymerizations with styrene (St) or isoprene. 10,11,14 However, no copolymers of BzA and its derivatives with vinyl ethers (VEs), which have high cationic polymerizability, have been obtained, 11 although carbocation from BzA derivatives were proven to initiate living polymerization of alkyl vinyl ethers.…”
Section: Introductionmentioning
confidence: 99%
“…This presumption was substantiated by the fact that o-vinylbenzaldehyde gave a cyclopolymer with cationic catalysts. 3 formation of the six-membered ring unit. It was of particular interest to compare the reactivities of these aldehyde groups.…”
Section: Polyacetalmentioning
confidence: 99%
“…22 However, the cationic polymerization of these compounds has rarely been studied due to difficulty in their polymerization as reported decades ago. 23, 24 We recently reported the successful controlled cationic copolymerization of BzAs with alkyl vinyl ethers (VEs) using weak Lewis base-assisting initiating systems for the first time. 25,26 Nearly alternating copolymers with controlled molecular weights and narrow molecular weight distributions (MWDs) were obtained from the appropriate combinations of monomers, i.e., VEs with lower reactivity and aldehydes with larger basicity (Scheme 1).…”
Section: ■ Introductionmentioning
confidence: 99%